Coastal shipping during the pandemic: Spatial assessment of the demand for passenger maritime transport - Boile, Maria; Theofanis, Sotirios; Perra, Vasiliki-Maria; Kitsios, Xenophon (Frontiers in Future Transportation, 2023)
Coastal shipping plays a key role in insular regions, ensuring economic, territorial and societal cohesion at national and regional level, supporting the transport of passengers, vehicles and goods. For Greece, passenger maritime transport is essential, considering its lengthy coastline (about 15,000 km) and its numerous islands, scattered within its territorial waters. The pandemic led to significant disruption of transport services, especially in ferry operations, affecting the increasing trends of the sector observed until the start of 2020. The demand for passenger traffic was almost halved during 2020, although a gradual recovery started in 2021. Supply was adjusted to sufficiently cover the demand. However, the services provided are mostly determined by the terms of the public service obligations (PSOs) that are announced by the responsible National Authority and which had to be further enhanced during the pandemic. This paper investigates the demand and supply of the Greek coastal shipping system before and during the pandemic, attempting to highlight the main issues and provide relevant information that can support policy and decision making as well as the implementation of relevant strategies and measures with the aim to improve the provided services in the sector.